Equipment Criticality Analysis to Determine Asset Integrity Management System Scheme in Supporting Production Optimization Scenarios in the Aeging Field - Andryanto, Donny; Dhaneswara, Donanta (Journal of Materials Exploration and Findings, 2025)
This research investigates the production decline and cost increase in the X&Y oil and gas fields from 2022 to 2023. Production fell by 34%, while production costs per barrel rose by 79%. To address these issues, a series of optimization processes are proposed. These aim to restructure and enhance the production facilities to reduce current production costs. The optimizations include reducing pressure at the PPP Platform in 2024. Additional steps include shutting down CPP-ORF 14” pipelines and most processes at CPP 2 Platform by 2027 to convert it into an accommodation platform. Further, the plan involves optimizing the release of two FSO units and directing oil production to ORF via a 16” pipeline by 2028. This study also emphasizes the need for Asset Integrity Management to implement optimization scenarios. This measure aims to reduce maintenance costs, ensure plant integrity, and update maintenance programs based on equipment criticality assessments.